Radiographic finding of sunray appearance as a sign of malignant mandibular lesion: a case report - Alfina, Risca; Rahman, Fadhlil Ulum Abdul; Yunus, Barunawaty; Ariestiana, Yossy Yoanita (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2025)
Objectives: To report the “sunray” appearance on panoramic radiography as a sign of malignancy lesions of the mandible. Case Report: A 40 year old female patient came to the Hasanuddin University Dental Hospital with the main complaint of facial swelling which causes an asymmetrical appearance and hard consistency on palpation. Mucosa around the second right premolar to the third right molar is reddish with an irregular border. The patient was referred to the radiology department for panoramic radiography and MRI. The panoramic radiograph revealed a mixed radiolucent-radiopaque lesion in tooth 35 involving ramus to the coronoid process. PDL space was irregular widening at 36, 37, and 38. The "sunray” appearance was seen from the ramus extending to the coronoid process. On the MRI, a mass on the submandibular gland pushed and narrowed the sublingual, parapharyngeal, and masticator space, destroying the mandible on the left side. These radiologic findings strongly suggest a malignancy involving the jawbone. Conclusion: The findings of a mandibular malignancy in the form of a “sunray” appearance on panoramic radiography need to be confirmed with an MRI examination to determine the consistency and extent of the lesion to the surrounding tissue. A comprehensive examination is necessary to properly diagnose mandibular malignant lesions so that the most suitable treatment plan can be determined.